If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-3x-4x=-64
We simplify the equation to the form, which is simple to understand
x-3x-4x=-64
We move all terms containing x to the left and all other terms to the right.
+1x-3x-4x=-64
We simplify left and right side of the equation.
-6x=-64
We divide both sides of the equation by -6 to get x.
x=10.6666666667
| x+5=4x-60 | | -c+3=-2c+6 | | 16a^2-121b^2=0 | | 6x-12+4x-1=-x-7+12-3x+5 | | 0=n^2+200 | | -5n+4=5n+34 | | 2x-26=x+3 | | 8(4x-12)=8x-18 | | 9f+7=-8f+24 | | 2x-29=x+2 | | 2x-10=5x+9 | | 0=n^2+60n+1600 | | 2x-27=x+2 | | 8(x+2)=3(x-5)-7(x+3) | | 5p+7+14p+40= | | 3q=3q-3 | | 0=n*2+60n+1600 | | 2x-27+x+2= | | .19-5m=34 | | .75m+3=-12 | | (2x-27)+(x+2)= | | 2.4=-8(.3p+9) | | 6x+13=-51-10x | | 4(x+3)-2(-x+3)=6-x | | y=x^2-6x+10 | | 4(2h+3)=6 | | 16=.33t+8 | | 8b+2=34 | | 9w+3=39 | | .2x+4=9 | | 4x+2+36x+8= | | 5t^2-26tx+5x^2=0 |